(untitled) (The International Journal for Scientific Research, 2023)
This paper deals with the design of speed and torque control of DC motor drive. The PI control scheme is proposed for the system, and it is usually used in DC motor drives. The proposed control schemes guarantee the asymptotic stability of the closed-loop system. The converter that is used in the system is a 4-quadratic switch-mode DC-DC converter. The design is based on a small signal model and verified using a large signal model. To illustrate the developed control schemes, the performance of the closed loop system is simulated using MATLAB. The simulation, analysis, and discussion are introduced to present the efficiency of the scheme.